Evaluation of techniques to reduce deer and Elk damage to agricultural crops. (21st February 2014) - Johnson, Heather E.; Fischer, Justin W.; Hammond, Matthew; Dorsey, Patricia D.; Walter, W. David; Anderson, Charles; VERcauteren, Kurt C.
ABSTRACT Mule deer (Odocoileus hemionus) and Rocky Mountain elk (Cervus elaphus nelsoni) provide important recreational, ecological, and economic benefits, but can also cause substantial damage to agricultural crops. Cervid damage to agriculture creates challenges for wildlife agencies responsible for minimizing crop depredation while maintaining healthy deer and elk populations. Sunflower producers in southwestern Colorado, USA, have experienced high deer and elk damage and were interested in temporary methods to reduce damage that were cost‐effective for rotational crops. To address this challenge, we investigated 3 temporary, non‐lethal exclusion and repellent techniques for reducing deer and elk damage to sunflowers: 1) a polyrope electric fence, 2) the chemical repellent Plantskydd™, and 3) a winged fence. During July through October 2011 and 2012, we used a randomized block design to test the efficacy of these techniques by quantifying cervid damage to sunflowers and the number of deer and elk tracks traversing treatment and control plot boundaries. Using generalized linear mixed models we found that polyrope electric fences reduced deer and elk damage and presence within plots, while the repellent and winged fences did not reduce ungulate activity. Polyrope electric fences may be a suitable tool in areas where wildlife management agencies want to maintain deer and elk populations but reduce seasonal damage by cervids to high‐value crops. In Colorado, use of an effective exclusion technique such as polyrope electric fence could also decrease the need for lethal depredation permits and damage compensation payments, and increase satisfaction among producers and the public. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.